2020
DOI: 10.1097/ijg.0000000000001672
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative High-speed Assessment of Droplet and Aerosol From an Eye After Impact With an Air-puff Amid COVID-19 Scenario

Abstract: Purpose: To quantify aerosol and droplets generated during noncontact tonometry (NCT) and assess the spread distance of the same. Methodology: This was an experimental study on healthy human volunteers (n=8 eyes). In an experimental setup, NCT was performed on eyes (n=8) of human volunteers under normal settings, with a single and 2 drops of lubricant. High-speed shadowgraphy, frontal lighting technique, and fluorescein analysis were used to detect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Finally, both the fingers from Rayleigh–Taylor as well as the ligaments from the bag formation undergo Rayleigh–Plateau instability and disintegrate into ellipsoidal droplets measuring 0.2–3 mm. In a previous study, 14 we measured the mean airflow in a standard hospital setting as 0.5–1 m/s. The maximum spread radius 20 of the smallest droplets (0.2 mm in size) generated during tonometry is ∼0.5 m, which is larger than the distance between the patient and the tonometer (11 mm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, both the fingers from Rayleigh–Taylor as well as the ligaments from the bag formation undergo Rayleigh–Plateau instability and disintegrate into ellipsoidal droplets measuring 0.2–3 mm. In a previous study, 14 we measured the mean airflow in a standard hospital setting as 0.5–1 m/s. The maximum spread radius 20 of the smallest droplets (0.2 mm in size) generated during tonometry is ∼0.5 m, which is larger than the distance between the patient and the tonometer (11 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Since viruses like human T-cell leukemia/lymphotropic virus type III (HTLV-III) 11 and severe acute respiratory syndrome (SARS)-coronavirus (CoV)-2 12,13 can be present in human tears, it was conjectured that such an event is a possible source of infection. Shetty et al 14 showed using clinical studies that droplets are visibly ejected in the case of watery eyes but not for dry eyes. However, the clinical studies do not attempt a physical analysis of the underlying fluid dynamics involved in the tear film breakup and tear ejection.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, the transmissibility of the Coronavirus disease 2019 (COVID-19) from the ocular surface remains indefinite; thus, contact and aerosol-generating procedures are best avoided to prevent transmission, particularly among eyes with high IOP 21 and high tear volume. 22 Thin CCT underestimates IOP, while thick CCT overestimates IOP. Thin CCT may then delay diagnosis of glaucoma and cause insufficient treatment and rapid progression of glaucoma; thus, CCT measurements should be addressed to properly comprehend the risk for glaucoma in each patient.…”
Section: Introductionmentioning
confidence: 95%
“… 16 Moreover, the transmissibility of the Coronavirus disease 2019 (COVID-19) from the ocular surface remains indefinite; thus, contact and aerosol-generating procedures are best avoided to prevent transmission, particularly among eyes with high IOP 21 and high tear volume. 22 …”
Section: Introductionmentioning
confidence: 99%
“…We operated on our first coronavirus or COVID-19 positive case (CPC), who had an extensive eyelid and canalicular tear and needed early surgery. While the risk of operating on a positive patient is high due to aerosols generated,[ 1 2 3 ] no team member refused to be a part of the surgery. We did have some hiccups which is expected given that it is our first such experience.…”
mentioning
confidence: 99%